Urology Practice in Low- to Middle-Income Countries - Mohammed Shahait (Société Internationale d’Urologie Journal)
The global burden of urological diseases is rising, particularly in low- and middle-income countries (LMICs) undergoing rapid demographic and epidemiological changes [...]